DNA damage-induced centrosome amplification occurs via excessive formation of centriolar satellites - Löffler, Harald; Fechter, Anne; Liu, Fang; Krämer, Alwin (Oncogene, 2013)
Centrosome amplification is a frequent phenomenon in malignancies and may facilitate tumorigenesis by promoting chromosomal instability. On the other hand, a centrosome inactivation checkpoint comprising centrosome amplification leading to elimination of cells by mitotic catastrophe has been described in response to DNA damage by ionizing radiation or cytostatic drugs. So far, the exact nature of DNA damage-induced centrosome amplification, which might be overduplication or fragmentation of existing centrosomes, has been controversial. To solve this controversy, we have established a method to distinguish between these two possibilities using A549 cells expressing photoconvertible CETN2-Dendra2. In response to various DNA-damaging treatments, centrosome amplification but not fragmentation was observed. Moreover, centrosome amplification was preceded by excessive formation of centrin-containing centriolar satellites, which were identified as de novo-generated atypical centrin dots staining positive for centriolar satellite markers but negative or only weakly positive for other established centrosomal markers, and which could be verified as centriolar satellites using immunogold electron microscopy. In line with this notion, disruption of dynein-mediated recruitment of centrosomal proteins via centriolar satellites suppressed centrosome amplification after DNA damage, and excessive formation of centriolar satellites could be inhibited by interference with Chk1, a known mediator of centrosome amplification in response to DNA damage. In conclusion, we provide a model in which a Chk1-mediated DNA damage checkpoint induces excessive formation of centriolar satellites constituting assembly platforms for centrosomal proteins, which subsequently leads to centrosome amplification.